PENINGKATAN MOTIVASI IBU RUMAH TANGGA UNTUK MEMANFAATKAN TANAMAN OBAT KELUARGA (TOGA) - Kusumawaty, Y.; Khaswarina, S. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
The tendency of society to return to nature have increased interest in herbal remedies. This condition provides business opportunities for variety of medicinal plants including the cultivation of family medicinal plants (TOGA). The purpose of this community service activity was to increase people's motivation to exploit the business opportunity of herbal plants collectively. The program was conducted in three steps: (1) approaching the problems faced by mothers in managing medicinal plants through interviews with community leaders; (2) conducting training on the utilization of variety of crops into simple remedies and (3) evaluation of the training outcomes and motivation of training participants to develop the cultivation and processing of medicinal plants. The results showed that participants were motivated to develop medicinal plant business. Tips shared on how to manage medicinal plant gardens in groups were helpful to reduce individual workload. In general, the implementation of training activities on the utilization of Family Medicinal Plants (TOGA) was quite successful. This can be seen from the participants’ request that this activity can continue to support them. Cultivation of medicinal plants is suitable as an alternative for housewife empowerment because it can be done without leaving the important role as a mother.